INVESTOR’S BEHAVIOUR TOWARDS COMMODITY MARKET - Thriveni S.R; Nazeer, Dr. Irshad (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Earning money is important it is also important to make money work for you through investments in better markets can fulfil this desire. . investing in better markets can fulfil this desire. Investors invest their hard-earned money keeping the intention to earn good returns. Investors choose their investment avenues based on their financial goals. All the investor's goals vary from person to person. Investor based on their intentions collect the information and form their perception and attitude towards the investment options available in the market. Investment decisions are influenced by internal and external factors. Internal factors demographic factors, personal factors, external factors and behavioural biases. Such as inflation, market conditions, regulatory system and political conditions of the country. Commodity markets offer investment opportunities for retail investors to invest in Commodity exchange-traded funds. Commodity Exchange Traded Funds (ETFs) are one of the investment avenues available to investors who want to be exposed to the commodity market and earn good returns. Commodity Exchange Traded Funds are funds which invest in commodities, such as precious metals, agricultural commodities, hard metals and Energy and livestock etc., Commodity prices are influenced by the performance of the economy or the forces of demand and supply. Instability in commodity prices can give investors leverage which helps them generate revenue. The commodity market operates through various platforms, including commodity exchanges like the Multi Commodity of India(MCX) and the National Commodity and Derivatives Exchange (NCDEX). These platforms enable standardized contract agreements for trading. According to the traditional theory of finance, investor exhibit rationality in their investment decisions but normally human nature is often irrational, leading to biased decisions based on psychological expectations. The study objective is to understand the investment behaviour of retail investors towards commodity markets and commodity Exchange Traded Funds. Primary data was collected through a structured questionnaire and secondary data was gathered from researched articles, journals and online platforms.